Land management mechanism, its tasks and functions - Dorosh, A.; Svyrydov О. (Land Management, Cadastre and Land Monitoring, 2024)
The concept of a land management mechanism as a set of tools and levers, the coordinated interaction of which provides influence on the formation and development of land use, has been proposed. It has been proven that the land management mechanism is an important component of the land management system, which ensures the rational use and protection of land. The main tasks of the land management mechanism are to create legal, economic, organizational and technical conditions for effective land use. This mechanism is aimed at ensuring a balance between the economic, ecological and social aspects of the use of land resources. It is substantiated that the functions of the land management mechanism are derived from the functions of land management, since it is through this mechanism that land relations are regulated. The regulatory function ensures control and stimulation of rational land use through the development of documentation and management decisions. The investment function informs about the investment attractiveness of various types of land use and evaluates the effectiveness of investments. The incentive function encourages economic benefit from the productive use of land, and the information function disseminates objective information about the most profitable and ecological ways of using land. The effective functioning of the land management mechanism allows resolving conflicts related to the use of land resources, contributes to increasing the productivity of agricultural production, and also ensures the sustainable development of territories. In addition, the land management mechanism plays an important role in the planning and development of infrastructure, urbanization and solving issues related to land management. Key words: land management, land use, land management mechanism, functions of land management mechanism, tasks of land management mechanism